The Influence of the First Thousand Days of Life on Establishing Determinant Behaviors for Dental Caries in Childhood - Luiz Gustavo Teixeira Martins; Eliane Traebert; Abelardo Nunes Lunardelli; Sandra Espíndola Lunardelli; Jefferson Traebert (Association of Support to Oral Health Research (APESB), 2021)
Objective: To study the influence of the first thousand days of life on establishing determinant behaviors for dental caries in childhood. Material and Methods: Longitudinal retrospective study involving 664 children born in 2009 living in a southern Brazilian municipality was carried out. Data was collected through interviews with mothers and through child's health card. Dependent variables were 1) tooth brushing onset after two years of age; 2) absent tooth brushing or once a day; 3) tooth brushing without adult supervision; 4) not having gone to the dentist until the age of 6; and 5) seek for dental services due to toothache at 6 years of age, over the last 30 days. Bivariate and multivariate analyses were performed using Poisson Regression to estimate relative risks (RR) and respective confidence intervals at the 95% accuracy level. Results: Mothers with lower schooling at child's birth presented a higher risk of "child's tooth brushing onset only after two years of age", "brushing the teeth once a day only or not brushing" and with "child not having gone to the dentist until the age of 6". Mothers who did not have a job when the child was born were associated with "not having gone to the dentist until the age 6". Children with gastroesophageal reflux who underwent hospitalization for more than 2 days under age 2 were associated with "seeking dental services because of pain at 6 years of age over the last 30 days". Conclusion: Higher risks of some determinant behaviors related to dental caries were associated with variables of the period of the first thousand days of life.